Cost-effectiveness of strategies to improve delivery of brief interventions for heavy drinking in primary care: results from the ODHIN trial. (17th September 2018) - Angus, Colin; Li, Jinshuo; Romero-Rodriguez, Esperanza; Anderson, Peter; Parrott, Steve; Brennan, Alan
Abstract: Background: Screening and brief interventions (SBIs) for heavy drinking are an effective and cost-effective approach to reducing alcohol-related harm, yet delivery rates remain low. This study uses trial data to estimate the cost-effectiveness of alternative strategies to increase SBI delivery. Methods: Data from a large cluster-randomized trial were combined with the Sheffield Alcohol Policy Model, a policy appraisal tool, to estimate the cost-effectiveness of eight strategies to increase SBI delivery in primary care in England, Poland and the Netherlands: care as usual (control), training and support (TS), financial reimbursement (FR), referral of patients to an online brief intervention (eBI) and all combinations of TS, FR and eBI. cost-effectiveness was assessed from a healthcare perspective by comparing health benefits (measured in Quality-Adjusted Life Years) with total implementation costs and downstream healthcare savings for each strategy over a 30-year horizon and calculating Incremental cost-effectiveness ratios (ICERs). Results: All trialled strategies were cost-effective compared to control. TS combined with FR was the most cost-effective approach in England (more effective and less costly than control) and Poland (ICER €4632 vs. next-best strategy). This combination is not cost-effective in the Netherlands, where TS alone is the most cost-effective approach (ICER €3386 vs. next-best strategy). Conclusions: Structured TS, financial incentives and access to online interventions are all estimated to be cost-effective methods of improving delivery of alcohol brief interventions. TS and FR together may be the most cost-effective approach, however this is sensitive to country characteristics and alternative BI effect assumptions. Trial registration: ClinicalTrials.gov trial identifier: NCT01501552